Porous YSZ Ceramics Reinforced by Different Kinds of Fibers. Issue 5 (19th November 2013) - Lang, Ying; Wang, Chang‐An; Tie, Shengnian
<x xml:space="preserve">Abstract</x> Porous YSZ ceramics reinforced by different fibers were prepared by gel‐casting with 15% solid content and pressureless sintering. The four kinds of fibers (mullite, aluminosilicate, Al2O3, and YSZ fibers) were added into the YSZ ceramics with the same 10% vol content. After sintered at 1500°C for 2 h, aluminosilicate and mullite fibers could not be found in the samples of porous YSZ ceramics, which showed they reacted with YSZ ceramics at high temperature, while YSZ and Al2O3 fibers still kept perfect after sintering. Furthermore, the influences of fiber content, sintering temperature, porosity of matrix materials on compressive strength and porosity of the porous YSZ ceramics were studied. The results showed that Al2O3 fiber showed more obvious reinforcing effect than YSZ fiber on porous YSZ ceramics. The fiber‐reinforcing effects depend on fiber content, sintering temperature, and porosity of matrix materials. The fiber addition can improve the shrinkage behavior of porous ceramics during sintering and strengthen the skeleton of porous ceramics.